Edukasi Bencana Melalui Syair Didong Uten Karya Ceh Sali Gobal dalam Pengurangan Risiko Bencana di Kecamatan Kebayakan Kabupaten Aceh Tengah - Ditha Ramadhani*; Sulastri Sulastri; Muhammad Dirhamsyah (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Central Aceh district is an area that has a high risk index for landslides. Besides that, Central Aceh is also rich in local wisdom, one of which is didong which has many poems.This study aims to investigate the messages of local wisdom about disaster risk reduction in didong uten poetry and obtain an integration model of didong uten poetry in learning that can be accepted by teachers and students at high school. The research model used is the Etnografi research model by Spradley which broadly consists of five stages, namely: First, a) have an ethnographic project, b) ask an ethnographic question, c) collect ethnographic data, d) make ethnographic notes, e) analyzing ethnographic data. This study has validated media experts in the form of didong uten poetry and obtained an average score of 97.3% with the criteria "very feasible", material expert validation in the form of disaster education and disaster risk reduction obtained an average score of 66.6% with the "feasible". Based on the results of the implementation of the instrument, the final score on disaster education (knowledge) is 62.65, the value of disaster education (attitude) is 77.68, the final value of didong uten poetry is 53.98, and the final value of disaster risk reduction is 68.7. conclusion after conducting ethnographic research interviews from 5 resource persons is that didong uten poetry can be integrated into school subjects such as geography, sociology, Indonesian language, besides that didong uten poetry can also be extracurricular at school